Digital Analysis Method for Predicting Flood in A River of Lhoksukon Aceh North Indonesia - Wijaya, Riki (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2023)
The major floods that occurred in 2022 in Lhoksukon, North Aceh, Indonesia, had a severe impact on infrastructure damage and loss of life, making it necessary to analyze and predict its impact. In this regard, digital methods can effectively analyze and predict the impact of such natural disasters. The digital method is processing digital data through software to produce the desired information. Based on the results of the digital analysis, it has been found that the flood discharge in the Lhoksukon area of North Aceh is around 1848 m3/second with a flow velocity of about 3.484 m/second. This high flow velocity can cause significant damage to the infrastructure in the affected areas. The flood height in the river area ranges from 9.545 m from the riverbed, which is a cause for concern. The increase in water level will cause an expansion of the inundation area in the river area, which can lead to further damage. Therefore, the results of this study can be used to develop effective flood mitigation strategies and infrastructure planning in the affected areas. Additionally, the study's findings can be used to develop early warning systems to alert people in the affected areas to evacuate before the floods reach dangerous levels.